2014
DOI: 10.3390/ijerph111111325
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Toxicity Profile of Electronic and Tobacco Cigarettes, Smokeless Tobacco and Nicotine Replacement Therapy Products: E-Liquids, Extracts and Collected Aerosols

Abstract: The use of electronic cigarettes (e-cigs) continues to increase worldwide in parallel with accumulating information on their potential toxicity and safety. In this study, an in vitro battery of established assays was used to examine the cytotoxicity, mutagenicity, genotoxicity and inflammatory responses of certain commercial e-cigs and compared to tobacco burning cigarettes, smokeless tobacco (SLT) products and a nicotine replacement therapy (NRT) product. The toxicity evaluation was performed on e-liquids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 53 publications
10
91
2
2
Order By: Relevance
“…Bahl et al (2012) and Misra et al (2014)). Unlike tobacco cigarettes, which have defined nicotine yields on the packaging, the nicotine content of E-liquids is simply labelled as 'low', 'medium', or 'high'; the precise concentration is not defined.…”
Section: Introductionmentioning
confidence: 99%
“…Bahl et al (2012) and Misra et al (2014)). Unlike tobacco cigarettes, which have defined nicotine yields on the packaging, the nicotine content of E-liquids is simply labelled as 'low', 'medium', or 'high'; the precise concentration is not defined.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Misra et al (2014) found no cytotoxicity or mutagenicity of EC aerosols, but found high cytotoxicity and mutagenicity of CC smoke in human lung epithelial cells (A549). Also, Scheffler et al (2015b) discovered reduced viability and increased oxidative stress when human bronchial epithelial (NHBE) cells were exposed to EC humectants, but much lower viability and higher oxidative stress when the same cells were exposed to CC smoke (see also Taylor et al 2016 for similar results).…”
Section: Cellular Level Effectsmentioning
confidence: 99%
“…There have been reports of cytotoxicity caused by smokeless tobacco products such as gutkha (Avti et al, 2010), khaini (Das et al, 2013), Sudanese toombak (Costea et al, 2010), American moist snuff (Misra et al, 2014), Swedish moist snuff (Coggins et al, 2012, Costea et al, 2010, Kentucky reference moist smokeless tobacco product (Lombard et al, 2010) and commercial chewing tobacco (Coppe et al, 2008). The present study is the first assessment of cytotoxicity induced by tobacco constituents of pituri as a means of investigating its potential carcinogenicity.…”
Section: Introductionmentioning
confidence: 96%
“…There are numerous reports on in vitro cytotoxic effects of commercially available smokeless tobacco products such as Swedish snus (Coggins et al, 2012, Costea et al, 2010, American moist snuff (Misra et al, 2014), commercial chewing tobacco (Coppe et al, 2008) and Kentucky reference smokeless tobacco product (Lombard et al, 2010). There have been reports of cytotoxicity caused by Indian manufactured smokeless tobacco such as gutka (Avti et al, 2010) and khaini (Das et al, 2013).…”
Section: Toxicity Of Smokeless Tobacco Productsmentioning
confidence: 99%
See 1 more Smart Citation